Answer:
Recursive form of sequence is given by f(n) = f(n-1) - 3
Step-by-step explanation:
The explicit form of sequence is given as
f(n) = −3n + 2
So nth term is given by
f(n) = −3n + 2
(n-1)th term is given by
f(n-1) = −3(n-1) + 2
We have
f(n) - f(n-1) = −3n + 2 - (−3(n-1) + 2)
f(n) - f(n-1) = −3n + 2 +3(n-1) - 2
f(n) - f(n-1) = −3n + 2 +3n -3 - 2
f(n) - f(n-1) = -3
f(n) = f(n-1) - 3
Recursive form of sequence is given by f(n) = f(n-1) - 3
Answer:a:20 thats the one
Step-by-step explanation:
OB. √26
OC. √28
OD. √/22
The answer fam is........ √26